Therapeutic farriery of the hind feet for horses with hindlimb orthopaedic injuries. (2nd January 2021) - Clements, Peter
Abstract : Low heels and negative plantar angles in the hind feet are the most common hind foot conformational abnormality. A causal relationship has been demonstrated between these conditions and hindlimb lameness. It is important these abnormalities are recognised during thorough orthopaedic examinations, so they can be quantified with radiography and appropriately treated with therapeutic farriery to restore optimal hoof conformation, balance and function. This is an essential part of a holistic approach to treating horses with hindlimb lameness. Farriery intervention for these abnormalities involves returning the plantar half of the foot to a load-sharing plane between the frog and heels, restoring phalangeal alignment and providing increased ground surface plantar to the centre of rotation of the distal interphalangeal joint.